Soil type influences crop mineral composition in Malawi - Joy, Edward J.M.; Broadley, Martin R.; Young, Scott D.; Black, Colin R.; Chilimba, Allan D.C.; Ander, E. Louise; Barlow, Thomas S.; Watts, Michael J. (Elsevier, 2015)
Food supply and composition data can be combined to estimate micronutrient intakes and deficiency risks among populations. These estimates can be improved by using local crop composition data that can capture environmental influences including soil type. This study aimed to provide spatially resolved crop composition data for Malawi, where information is currently limited. Six hundred and fifty-two plant samples, representing 97 edible food items, were sampled from N150 sites in Malawi between 2011 and 2013. Samples were analysed by ICP-MS for up to 58 elements, including the essential minerals calcium (Ca), copper (Cu), iron (Fe), magnesium (Mg), selenium (Se) and zinc (Zn). Maize grain Ca, Cu, Fe, Mg, Se and Zn concentrations were greater from plants grown on calcareous soils than those from the more widespread low-pH soils. Leafy vegetables from calcareous soils had elevated leaf Ca, Cu, Fe and Se concentrations, but lower Zn concentrations. Several foods were found to accumulate high levels of Se, including the leaves of Moringa, a crop not previously been reported in East African food composition data sets. New estimates of national dietary mineral supplies were obtained for non-calcareous and calcareous soils. High risks of Ca (100%), Se (100%) and Zn (57%) dietary deficiencies are likely on non-calcareous soils. Deficiency risks on calcareous soils are high for Ca (97%), but lower for Se (34%) and Zn (31%). Risks of Cu, Fe and Mg deficiencies appear to be low on the basis of dietary supply levels.